감귤박 에탄올추출물과 열수추출물의 영양성분 및 항산화 활성 - 송연우(YeonWoo Song); 문근식(Keun Sik Moon); 김소미(Somi Kim Cho) (Han'guk Sikp'um Yŏngyang Kwahakhoe chi, 2013)
The objective of this study was to evaluate the effect of extraction methods on the antioxidant activity of Citrus unshiu pomace. For this purpose, two kinds of citrus pomace (CP)s, whole fruit CP and pulp CP, were used for preparing the extracts with hot water or 70% ethanol. It is well-known fact that whole fruit CP has more calories and carbohydrates, although moisture content is higher in pulp CP. Further, whole fruit CP extracts have higher levels of total phenolic contents compared to CP extracts. In addition, DPPH and alkyl radical scavenging activities were also higher in whole fruit CP, especially in ethanolic extracts. Our results based on liquid chromatography-mass spectrometer showed that 70% ethanolic extract of whole fruit CP has the maximum levels of nobiletin and tangeretin contents. The levels of naringin, which is known as an antioxidant flavonoid, was determined only in the 70% ethanolic extract of whole fruit CP. This result, however, is consistent with the observed DPPH and alkyl radical scavenging activities. We had also performed a gas chromatography analysis that showed all the four extracts contained the compound hydroxymethyl furfural. Significantly, this compound has been reported to have antioxidant activity. Taken together, findings of this study indicate that ethanolic extraction of whole fruit CP is a good source of antioxidant compounds and hence the same could be utilized as an important method to obtain such beneficial compounds on an industrial scale. 본 연구는 감귤박의 생리기능성을 탐색하고자 통과 감귤박과, 과피를 제거한 과육 감귤박을 열수와 에탄올로 각각 추출하여 일반성분 및 항산화 활성을 측정하였다. 감귤박의 일반성분을 측정한 결과, 열량과 탄수화물은 통과 감귤박이 더 높았으며 수분은 과육 감귤박이 더 높은 것으로 나타났다. 총 폴리페놀 함량은 추출 용매에 따른 차이는 없었으나, 과피를 포함하고 있는 통과 감귤박이 더 높은 함량을 나타냈다. ESR을 이용한 DPPH 라디칼 소거능과 alkyl 라디칼 소거능 측정 결과, 과육보다는 통과 감귤박의 활성이 더 높았으며, 열수추출물보다는 에탄올추출물이 활성이 높게 측정되었다. Liquid chromatography를 이용한 플라보노이드 함량 분석 결과, naringin은 통과 에탄올추출물에서만 검출되었으며, 또한 nobiletin과 tangeretin의 함량이 통과 에탄올추출물에서 높게 나타났다. GC 분석 결과를 토대로 감귤박 추출물의 항산화 활성은 플라보노이드뿐만 아니라 HMF와 maltol에 기인할 수 있음을 나타냈다. 따라서 과피를 포함하고 있는 통과 감귤박은 기능성 식품을 개발하는 데에 있어서 높은 활용 가치가 있는 것으로 사료된다.